Focusing a shock wave; microscopic structure of the phenomenon - Walenta, Z.A.; Orzeński, J. (Archives of Mechanics, 1998)
The problem of focusing a shock wave after its reflection from a concave wall is considered experimentally (in a shock tube) and numerically (employing the Direct Simulation Monte-Carlo technique). Rarefied flow conditions make it possible to clarify both the size of the focus and the structure of its neighbourhood.